2023
DOI: 10.1021/acsmacrolett.3c00083
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Viscoelasticity and Toughening Mechanisms in Nanoclay-PNIPAAm Double Network Hydrogels

Abstract: We investigate the mechanical properties of a magnetic temperature-sensitive hydrogel at varying concentrations of covalent and physical cross-linking. The hydrogel consists of covalently cross-linked poly(N-isopropylacrylamide) (PNIPAAm), physically interacting nanoclay particles, and magnetic ferric oxide nanoparticles. The physical nanoclay network exhibits strong viscoplastic behavior, and we find that increasing nanoclay content improves both strength and toughness in the double network materials. We inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The physically cross-linked network formed is much weaker than a chemically cross-linked network, but most materials have a stable physical cross-linked network. Physical nanoclay networks exhibit strong viscoplastic behavior, and we found that the introduction of a nanoclay improves the strength and toughness of dual-network materials [ 26 ]. By utilizing these materials, a hydrogel was created which uses BIS and lithium magnesium silicate nanoparticles as cross-linking agents, with both chemically and physically cross-linked networks; this hydrogel is referred to herein as a magnetic, temperature-sensitive network (see Figure 1 b).…”
Section: Resultsmentioning
confidence: 99%
“…The physically cross-linked network formed is much weaker than a chemically cross-linked network, but most materials have a stable physical cross-linked network. Physical nanoclay networks exhibit strong viscoplastic behavior, and we found that the introduction of a nanoclay improves the strength and toughness of dual-network materials [ 26 ]. By utilizing these materials, a hydrogel was created which uses BIS and lithium magnesium silicate nanoparticles as cross-linking agents, with both chemically and physically cross-linked networks; this hydrogel is referred to herein as a magnetic, temperature-sensitive network (see Figure 1 b).…”
Section: Resultsmentioning
confidence: 99%